L’anabasi (tra alterne fortune) della fecondazione eterologa a dieci anni dalla l. n. 40/2004 (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
A punctual analysis on the former, strict ban on assisted reproduction with gamete donation in Italy – established by law no. 40/2004 – and its following, progressive “demolition” by the Italian Constitutional Court (especially by the recent judgement no. 162/2014). A reflection about the criteria applied by the Court, the role of the European Court of Human Rights and the future, desirable legislation on ethically sensitive subjects.
Keywords: Bioethics and legislation; European Court of Human Rights; assisted reproduction with gamete donation; Italian constitutional caseâ€law; reasonable balance